Survei Kemampuan Kondisi Fisik Peserta Kegiatan Ekstrakurikuler Sepakbola SMP - Alfaridhi, Fani; Nurrochmah, Siti (Sport Science and Health, 2021)
Abstract: The purpose of this study was to determine and assess the ability of the physical condition of the participants in the football extracurricular activities at SMP Negeri 15 Malang. This study used a quantitative descriptive survey design. The subjects of this study were 30 participants in extracurricular football activities at SMP Negeri 15 Malang. The data was collected using a test form measurement technique, namely a test of the ability of the physical condition in the form of a test of motion agility, movement speed, flexibility of motion and leg muscle explosive power. The results of data analysis on the participants of the extracurricular football activities at SMP Negeri 15 Malang included (1) shuttle run agility 43, 3% medium category (2) running speed 50 m 5.33% medium category (3) body flexibility sit and reach 43.3% medium category and (4) leg muscle explosive power standing board jump 33.3% moderate category. Based on the results of the study, it was concluded that the participants of extracurricular football activities at SMP Negeri 15 Malang, the physical condition of the agility element was included in the "medium" category, the element of running speed was included in the "medium" category, the flexibility element was included in the "medium" category, and the element of leg muscle explosive power was included in the "category" medium â€.Â Abstrak: Tujuan penelitian ini adalah untuk mengetahui dan mengkaji kemampuan kondisi fisik peserta kegiatan ekstrakurikuler sepakbola SMP Negeri 15 Malang. Penelitian ini menggunakan rancangan survei bentuk deskriptif kuantitatif. Subyek penelitian ini berjumlah 30 orang peserta kegiatan ekstrakurikuler sepakbola SMP Negeri 15 Malang. Pengumpulan data menggunakan teknik pengukuran bentuk tes yaitu tes kemampuan kondisi fisik berupa tes kelincahan gerak, kecepatan gerak, kelentukan gerak dan daya ledak otot tungkai.Hasil analisis data pada peserta kegiatan ekstrakurikuler sepakbola SMP Negeri 15 Malang antara lain (1) kelincahan shuttle run 43,3% kategori sedang (2) kecepatan lari 50 m 5,33% kategori sedang (3) kelentukan tubuh sit and reach 43,3% kategori sedang dan (4) daya ledak otot tungkai standing board jump33,3% kategori sedang. Berdasarkan hasil penelitian disimpulkan bahwa pada peserta kegiatan ekstrakurikuler sepakbola SMP Negeri 15 Malang kemampuan kondisi fisik unsur kelincahantermasuk kategori â€œsedangâ€, unsur kecepatan lari termasuk kategori â€œsedangâ€, unsur kelentukan termasuk kategori â€œsedangâ€, dan unsur daya ledak otot tungkai termasuk kategori â€œsedangâ€.